Consumption Model of Financial Products among Minangkabau and Chinese in Bank Nagari, Sumatra - Heryanto (2005)
The purpose of the present study are first to analyze the differences in customer product preferences between Minangkabau and Chinese customers of Bank Nagari. Second, to determine factors affecting the use of Bank Nagari products among Minangkabau and Chinese customers. Third, to determine the Minangkabau and Chinese consumption models. The sample size amount 216 customers consisted of Minangkabau would amount to 162 persons and Chinese would amount to 54 persons. Systematic sampling is applied in this study as it often yields sampling error which is smaller. Data analysis technique is use consisted of factor analysis, cluster analysis, and logistic regression. Results of this study indicate the characteristics of Minangkabau customers are divided to three which are sociable (60%), supportable (30%) and friendly (10%). Similarly, there are also three types of Chinese customers namely supportable (60%), sociable (23%) and friendly (17%). The Minangkabau customers can be concluded as having social characteristics that seek for sympathy and reassurance, dependable. excited, institutes values of fun and enjoyment in life as well as warm relationships with others. These social signal are influenced by cultural values, which have been cultivated in the Minangkabau society. Conversely, Chinese customers assist and coalesce with one another to reach a common target. Such nature observed among the Chinese customers are not found in the Minangkabau customers. The result of logistics regression test for credit and saving products show partial significance at probability level of .050 and result of Hosmer and Lemershow Goodnes-of-Fit test show total significance at .050. Test result of ANOVA indicates that there is ethnic difference in the consumption of financial products. Thus, from the ethnic graph plot there are differences of the consumption pattern of credit and saving products. This means that Minangkabau customer have been using bank products optimally. On the contraly the plot graph of the ethnic Chinese usage of product is very strange. This means that Chinese customers only use credit products to support business activities. Cultural factor, saving and credit perception very much determine the consumption of ethnic Minangkabau and Chinese. The result of factor analysis indicates that there are three dimensions of saving products and three dimensions of credit products. The dimensions for saving products are labelled SSERVQUAL- I (certain time, sympathy and reassurance, dependability, saving service, accurate records, prompt service, willingness to help consumers, prompt response to consumer request, trusted employees, and safe feeling), 4 SSERVQUAL-2 (politeness, best interest at heart. convenient hours, up-to-date equipment and technology, visual appeal, well dressed and neat appearance and service type), and SSERVQUAL-3 (consumer information, adequate support, individual attention, personal attention and consumer needs). Whereas, the dimensions of credit products are labelled CSERVQUAL-I (certain time, sympathy and reassurance, dependability, credit senlice. accurate records, prompt service, willinpess to help consumers, prompt response to consumer request, trusted employees, safe feeling, and politeness). CSERVQUAL-2 (best interest at heart, convenient hours, up-to-date equipment and technology, visual appeal, well dressed and neat appearance and service type), and CSERVQUAL-3 (consumer information. adequate support, individual attention, personal attention and consumer needs). The findings of the study can be used by Regional Development Banks, Bankers and financial customers. It hopes to facilitate Regional Development Bank, in attaining optimal profit. Bankers would be able to offer optimal service to its customer. This will encourage customers to use banking products and services and provide alternatives to customers in the use of banking services. The study could also be used in identifying and developing relevant policies in helping the traders (especially small traders) managing credit and savings.